Patient Experience and Preference in Transradial versus Transfemoral Access during Transarterial Radioembolization: A Randomized Single-Center Trial - Liu, Lisa B.; Cedillo, Mario A.; Bishay, Vivian; Ranade, Mona; Patel, Rahul S.; Kim, Edward; Nowakowski, Scott F.; Lookstein, Robert A.; Fischman, Aaron M. (Journal of vascular and interventional radiology, 2019)
To determine patient preference for transradial access (TRA) or transfemoral access (TFA) after experiencing both. A randomized controlled crossover trial was conducted at a single institution. Thirty patients with hepatocellular carcinoma undergoing mapping and transarterial radioembolization (TARE) were enrolled to experience 1 TRA and 1 TFA procedure each, with randomization of which access approach was experienced first. Surveys assessing pain and quality of life (QOL) were administered after each procedure. Access site preference was collected after completion of both procedures. Twenty-two subjects (73.3%) preferred TRA, 4 (13.3%) preferred TFA, and 4 (13.3%) had no preference; 14 (46.7%) reported bruising after TRA, and 17 (53.3%) reported bruising after TFA. TRA was associated with significantly lower pain scores overall during the procedure, at the access site during the procedure, and in the recovery room compared with TFA (2.0 vs 2.9, P = .0046; 2.0 vs 3.0, P = .0004; 2.1 vs 2.9, P = .0357). Pain score after discharge was not significantly different (1.4 vs 1.5, P = .4235). QOL scores were not significantly different between TRA and TFA. No significant differences were found for fluoroscopy time, air kerma, dose-area product, or procedure time between TRA and TFA for either mapping (P = .1442, P = .5871, P = .6667, P = .6131) or radioembolization (P = .8574, P = .2344, P = .1119, P =.8474). For radioembolizations, TRA had significantly shorter recovery times compared with TFA (108 min vs 153 min, P = .0193). Patients exhibited a strong preference for TRA. With TRA, patients experienced less periprocedural pain and shorter recovery times without significant differences in radiation exposure or procedure length.